Sistem Pakar Diagnosa Kelainan Stunting Balita Menggunakan Metode KNN Berbasis Web - Wulandari, Amalia Rizki; Avianto, Donny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Stunting in young children is a child nutrition problem in Indonesia. This research has the main objective of preventing and overcome it through a technique that can predict stunted babies based on data or information. This study using KNN method uses 125 test data and the value of k = 3 gives an accuracy of 96%. This includes 119 accurate predictions and 6 inaccurate predictions. The aim of this study is to predict the outcome of stunting in toddlers. If they fall into the stunting category, the parents of the toddler must pay more attention to the nutritional development of the toddler to be able to minimize the stunting rate in Indonesia.